2015
DOI: 10.1037/xlm0000072
|View full text |Cite
|
Sign up to set email alerts
|

Masked primes activate feature representations in reading aloud.

Abstract: Theories of reading aloud are silent about the role of subphonemic/subsegmental representations in translating print to sound. However, there is empirical evidence suggesting that feature representations are activated in speech production and visual word recognition. In the present study, we sought to determine whether masked primes activate feature representations in reading aloud using a variation of the masked onset priming effect (MOPE). We found that target nonwords (e.g., BAF) were read aloud faster when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 52 publications
3
13
0
Order By: Relevance
“…This finding aligns well with the results of a masked priming study by Mousikou, Roon & Rastle (2015) . They found that when initial phonemes in the target and in the prime differ just by one feature (voicing vs devoicing; e.g., /b/ vs /p/, /d/ vs /t/, /f/ vs /v/, /g/ vs /k/, /s/ vs /z/), there is a masked onset priming effect: target reading-aloud latencies are shorter compared to an unrelated control condition (BAV primed with biz is responded to faster than BAV primed with pez , which is in turn faster than in the control condition, i.e., BAV primed with suz ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This finding aligns well with the results of a masked priming study by Mousikou, Roon & Rastle (2015) . They found that when initial phonemes in the target and in the prime differ just by one feature (voicing vs devoicing; e.g., /b/ vs /p/, /d/ vs /t/, /f/ vs /v/, /g/ vs /k/, /s/ vs /z/), there is a masked onset priming effect: target reading-aloud latencies are shorter compared to an unrelated control condition (BAV primed with biz is responded to faster than BAV primed with pez , which is in turn faster than in the control condition, i.e., BAV primed with suz ).…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, our study shows that phonemes that share the place and the manner of articulation condition the rimes, and humans are faster to read words where onset-conditioning is effective than words where onset-conditioning is ineffective. Phoneme pairs in Mousikou, Roon & Rastle (2015) study (/b–p/, /d–t/, /f–v/, /g–k/, /s–z/) are equivalent to five out of seven classes that distinguish the measure 2b from the measure 2a in this study (two additional classes in this study are and ). That is, the grouping by both place and manner of articulation in this study resulted in phoneme pairs that are different on the voicing feature, but similar on all other features.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Finally, an even stronger prediction can be made. It has been found that in non-word strings, phonemic features show masked priming effects: the target B AF was read aloud faster when primed by p iz , with which it shares a [labial] feature in the onset /p/, than by suz , whose onset /s/ is unrelated ( Lukatela et al, 2001 ; Mousikou and Coltheart, 2014 ; Mousikou et al, 2015 ). This effect has so far not been shown for whole written forms; typh oid does not prime TYPH OON ( Rastle et al, 2000 ).…”
Section: Methodsmentioning
confidence: 99%
“…The lack of an effect in these studies is particularly surprising given the undisputed status of the oral articulator in the description of linguistic contrasts (Chomsky & Halle, 1968; Ladefoged & Maddieson, 1996). Another set of studies has uncovered feature-level effects for primary oral articulator as well as for voicing, evidenced both by modulations of production RTs (Gordon & Meyer, 1984, for voicing; Klein, Roon, & Gafos, 2015, for articulator; Mousikou, Roon, & Rastle, 2015, for voicing; Roon & Gafos, 2015, for both) and by modulations of the phonetic output of speakers (Goldinger, 1998; Nielsen, 2007; Tilsen, 2009; Yuen, Brysbaert, Davis, & Rastle, 2010) driven by (in)compatibility between recently perceived stimuli and utterances produced. It can be reasonably argued that the inconsistency in finding feature-level effects is due to the variety in the experimental tasks across the various studies, which included responding to an auditory cue based on learned cue-response pairs (Gordon & Meyer, 1984; Roelofs, 1999), responding to a visual cue in the presence of various distractors (Galantucci et al, 2009; Kerzel & Bekkering, 2000; Roon & Gafos, 2015), reading aloud with masked primes (Mousikou et al, 2015), and shadowing spoken stimuli (Mitterer & Ernestus, 2008).…”
mentioning
confidence: 99%